PROMOTING FRUIT CONSUMPTION THROUGH GRANOLA BARS OF A TROPICAL FLAVOUR - Kiat, Ian Chan Chun; Adnan, Siti Yusrina; Maliki, Saumon; Seleh, Aleena Ameera; Usit, Kimberly; Idek, Sirhajwan (LIFE: International Journal of Health and Life-Sciences, 2021)
The purpose of this research was to offer an alternative snack to school students with the introduction of granola bars that were made of famous local fruit, jackfruit. It was discovered that most school students preferred to eat unhealthy snacks and consumed less healthy meals such as vegetables and fruits. Hence, these granola bars were introduced as a healthier snack for them as a way of mitigating their obsession with snacks with fewer nutrients and higher calories. Jackfruit used as the main ingredient of this granola bar to offer a new flavour that the students might find very familiar and appealing as well as to promote these tropical fruits among the locals and possibly, tourists and foreign visitors. The subjects for this study were 30 respondents from a local neighbourhood who sampled this granola bar and rated it based on a specific set of criteria. Their opinions were analysed to study their level of approval of this snack. The findings showed that the respondents had positive responses on the product and some offered constructive feedback on how to commercially improve the product. It could be deduced that the jackfruit granola bar has the potential to be marketed as a healthy snack. However, more research should be done in determining how effective this product could be in tackling obesity among school teenagers.